Low-dose antibiotic prophylaxis has no significant impact on the stability of the intestinal microbiome in children with urogenital tract malformations under 1 year of age. Issue 4 (August 2020) - Strasser, C.; Spindelboeck, W.; Kashofer, K.; Oswald, J.; Haid, B.
Summary: Introduction: Accumulating data point at potentially lasting effects of early childhood therapeutic antibiotic exposure on the intestinal microbial. Little is known on the impact of low-dose longterm antibiotic prophylaxis on the developing intestinal microbiota in children during their first year of life. Objective: To investigate compositional changes of the intestinal microbiota by next generation sequencing based microbiome analysis and bacterial metabolites in longitudinally collected fecal samples. Study design: Twelve patients were analyzed in this prospective, longitudinal pilot study during a period of 70 days (sampling on days 0, 7, 14, 30, 70). Only transvaginally and term born babies, breastfed with no prior antibiotic exposure with urogenital malformation (vesicoureteral reflux and/or upper urinary tract dilatation) were included into the study. Seven patients received antibiotic longterm prophylaxis with a second-generation cephalosporin and five did not. Sequencing of bacterial 16 S rRNA allowed for an analysis of the microbiome composition. The Principal coordinate analysis was performed for the evaluation of compositional profile. Furthermore, quantitative measurement of short chain fatty acids served as a proxy for the metabolic activity of the individual microbiome over the study time. Results: Analysis of observed species, Shannon Index and weighted Unifrac distances between timepoints revealed neither significant difference comparing the prophylaxis group versus the control group over the study period, nor significant changes within the groups over time. Principal coordinate analysis (PCoA) was performed for the evaluation of compositional profile. Also, no differences regarding the fecal SCFA content were found between the two groups (>0.05 at each tested point, Mann–Whitney Test). Discussion: Although there were interindividual compositional differences of the microbiome (cluster of bacterial composition) at the beginning of the observation, we did not observe significant longitudinal changes regarding both bacterial diversity and SCFAs in neither group. Over the study period, the patient's microbiome remained stable and resilient to the antibiotic exposure in terms of bacterial abundance and metabolism. Limitations to the study are the low number of patients included and the use of one single antibiotic (cefaclor). Conclusion: This is the first pilot study to demonstrate that long term low-dose antibiotic administration in children under one year of age does neither seem to influence the composition of the intestinal microbiota nor the quantities of bacterial fermentation products compared to untreated controls.